Not Yet Uhuru! Attuning to, re-imagining and regenerating transgressive decolonial pedagogical praxis across times Khapa(ring) the rising cultures of change drivers in contemporary South Africa - Kulundu-Bolus, Injairu M (Rhodes University, Faculty of Education, Department of Education, 2020)
The "Not yet Uhuru!" project positions itself as emancipatory African research in motion. It is a regenerative project that responds to the concern that whilst dominant discourses can articulate what African states, societies and economies are not, we still know very little about what they actually are. This is a particularly important gap in how research on Africa is conceptualised, especially as it pertains to apprehending the futures that the majority of young people on the continent are instinctively leading themselves to (Mbembe, 2001, p.9). The project seeks to forgo youth development strategies that act as a form of containment by prescribing normative aspects of citizenship on young leaders in ways that stifle the transgressive impulses they have reason to value (Kelley in Tuck and Yang, 2014, p.89). The study traces rising cultures in transgressive decolonial pedagogical praxis across times, as a way of "khapa(ring)" or accompanying the contemporary questions that Change Drivers in South Africa hold at the edge of their praxis. The study co-conspired with 21 Change Drivers in South Africa who were interested in regenerating and re-imagining what transgressive decolonial praxis could be in these times based on their experiences and learnings. Residential art-based workshops that explored each co-conspirator's offerings on the subject were distilled through the medium of film. These in turn were analysed using an "ethics of attunement" that produced songs as a reflexive pedagogical tool (Lispari, 2014, p.176). Sharing the resonate echoes of their praxis through song created another iterative reflection on their praxis two years after their initial offerings. As a way of weaving together the findings with a historical perspective, the resonant praxis of Change Drivers was put into conversation with three unconventional reviews that trace impulses around transgressive decolonial pedagogical praxis through fictional texts, political theory, poetry and intergenerational analysis, in order to surface resonant themes in praxis that echo across different times in history. This methodology sought to engage the question of the archive in pluriversal ways that appealed to different sensibilities, including the imaginative and hermeneutical, the traditionally analytical as well as the gifts of the lyrical and the erotic as different conceptual threads needed to resource the study. The reviews additionally spanned periods in the history of the continent that hold questions around precolonial and nascent colonial encounters, efforts to transgress within the liberatory movements and the intergenerational transmissions embedded in women and queer people's struggles. The themes that coalesced across times were leveraged into capsules of rising cultures that form an experimental nexus for the practice of transgressive decolonial pedagogical praxis that is already underway. These rising cultures were conceptualised as meditations on what it means to live into a vision of home built on the explorations of a paradigm of peace, humanness, pluriversality and decolonial love for those like and unlike us that strive for freedom on this continent (Dlala, 2017, p.52; Ndlovu- Gatsheni, 2013, p.142; Gqola, 2017, pp.197, 199). The rising ultures were reconciled through the creation of a litany that chronicles different refrains in transgressive decolonial pedagogical praxis in contemporary times. The litany is a tool that charts particular experiences that are surfacing as symptomatic. It seeks to generously surface the contradictions that we are collectively starting to see past, whilst acknowledging the tensions that we need to straddle, integrate and navigate towards greater synthesis. The litany is an honest way of acknowledging the glimpses gained of who we are in this present moment, while we continually challenge ourselves to open up to questions about what it means to grapple towards decolonial futures. This stance has influenced my role as an educator to unconditionally embrace movements that already underway, and reflect these back to those that I am conspiring with in ways that promote an ethic of care, solidarity and critical engagement. The study celebrates what is possible when we do not theorise ourselves away from the questions embedded in our current praxis. This is an ethic that chooses to stay close to the phenomena arriving at present, whilst acknowledging the historical experiences that echo it as a collective pulse for meaningful experimentation and praxis. The study believes by being faithful to ways of amplifying, integrating and reflecting what has been emerging for us over time, we build our capacity to better respond with an ethic centred on transgressive decolonial pedagogical praxis. This is the kind of accompaniment and care that Change Drivers across the continent deserve as they make the way towards a future worthy of their longing (Rushdie, 1999).
Keywords: Not Yet Uhuru (Arts Project); Anti-imperialist movements -- South Africa; Education -- Social aspects -- South Africa; Social change -- South Africa; Education -- Philosophy -- South Africa; Arts and society -- South Africa